Effects of a biological additive and sealing technique on the aerobic stability of whole-plant corn silage - M.E. Uriarte; K.K. Bolson; Ronald V. Pope (Kansas Agricultural Experiment Station Research Reports, 2001)
The objectives of this whole-plant corn study were to determine the effects of a biological additive and sealing technique on yeast and mold populations; and to examine the relationship between the microbial and chemical changes in the silages during exposure to air. Whole-plant corn was harvested at 80% milkline (36% DM), and ensiled at a density of 43 lb of fresh matter/ft3. One-half of the pre-ensiled forage was treated with a biological additive (A), which contained a mixture of bacteria and enzymes (supplied by Alltech, Inc., Nicholasville, KY); the other one-half of the pre-ensiled forage was the untreated control (C). One-half of the silos in the A and C groups were sealed immediately after filling (S = sealed) and the remaining silos were sealed 48 hr after filling (DS = delayed seal). Treatments consisted of combinations of the two main effects: additive (A and C) and sealing technique (S and DS). There were three, 5-gallon capacity, laboratory silos per treatment. Silos were opened after 150 days, and the chemical and microbial compositions and aerobic stability of the silages determined. All four silages were moderately stable during the period of exposure to air. The C, DS silage was the first to show a rise in temperature, occurring after 65 hr of exposure to air. The two DS silages were 48 hr less stable than their S counterparts, and the two A silages were 24 hr more stable than their C counterparts. Deterioration of the silages during exposure to air was accompanied by an increase in temperature and pH, a decrease in lactic acid content, and a rapid increase in the lactate-assimilating yeast population. Treatment with a biological additive significantly improved aerobic stability, but the mechanism of action was not evident. Delayed sealing after the silos were filled reduced the aerobic stability of the silages.; Dairy Day, 2001, Kansas State University, Manhattan, KS, 2001;
Keywords: Dairy Day; 2001; Kansas Agricultural Experiment Station contribution; no. 02-133-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 881; Dairy; Corn silage; Aerobic deterioration; Silage additives